SISTEM INFORMASI PENYEWAAN DAN JADWAL MAINTENANCE UNIT ALAT BERAT PADA PT. XYZ BERBASIS WEB - Puad, Lailyn; Gazali, Galli; -, Pariyadi (LP2M Universitas Nurdin Hamzah, 2024)
PT. XYZ (XYZ ) is a company engaged in the rental of heavy equipment. The problems faced by PT. XYZ include frequent errors in heavy equipment rental transactions, difficulties in data retrieval, challenges in dissementing information about equipment rentals, and problems in the management of equipment maintenance. The aim of this research is to design a web-based system for heavy equipment rental and maintenance schedulling system. The methodology used in the system design employs descriptive analysis with a case study approach. The system modeling tool used is the Data Flow Diagram. The prototype of this application is expected to facilitate PT. XYZ in conducting heavy equipment rental processes, easing maintenance scheduling, and generating reports. To achieve theses objective, the system will manage input data such as heavy equipment unit data, technician data, and service data. From these processes, the system will generate reports such as transcantion reports and maintenance reports